2009
DOI: 10.1080/14616700902812959
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Paper Out of News

Abstract: Using in-depth interviews, newsroom observation, and internal documents, this case study presents and analyses changes that have taken place at Finnish financial daily Taloussanomat since it stopped printing on 28 December 2007 to focus exclusively on digital delivery via the Web, email, and mobile. It reveals the savings that can be achieved when a newspaper no longer prints and distributes a physical product; but also the revenue lost from subscriptions and print advertising. The consequences of a newspaper'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…This illustrates both that a great deal of the time users seem to be in tune with the journalistic selection and that journalistic judgments are still the norm. Compared to other research that often points out and/or illustrates the potential of audience metrics and clicks (see, e.g., O'Neill & Harcup 2009;Phillips et al 2010, Thurman & Myllylahti 2009), the present study finds the effect, so far, to be heavily moderated by journalists and their news judgment. These findings may also be due to the specific media system, Democratic Corporatist (Hallin & Mancini 2004), where the press historically have been less commercialized as compared to the liberal system, although the division between commercial and public service media, as elaborated below, appears to be more important.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This illustrates both that a great deal of the time users seem to be in tune with the journalistic selection and that journalistic judgments are still the norm. Compared to other research that often points out and/or illustrates the potential of audience metrics and clicks (see, e.g., O'Neill & Harcup 2009;Phillips et al 2010, Thurman & Myllylahti 2009), the present study finds the effect, so far, to be heavily moderated by journalists and their news judgment. These findings may also be due to the specific media system, Democratic Corporatist (Hallin & Mancini 2004), where the press historically have been less commercialized as compared to the liberal system, although the division between commercial and public service media, as elaborated below, appears to be more important.…”
Section: Discussionmentioning
confidence: 60%
“…Thurman and Myllylahti (2009) report, in a study on a Finnish newsroom, that the traffic the site gets was a factor in writing and selecting stories. If traffic was slow, an attractive news story could be posted to get the numbers up.…”
Section: Clicks and Their Influence On News Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other things, it was suggested that print media especially would not fare well in the new digital era (Thurman and Myllylahti, 2009). Beliefs were also aired that the interactive potential of the internet would come to change, or at least influence, the practice of journalism, moving it from a one-to a two-way communication process (Chung, 2007(Chung, , 2008Hujanen and Pietikainen, 2004), leveling the playing field between journalist and reader, sender and receiver.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the Finnish newspaper Taloussanomat (Thurman & Myllylahti, 2009), the phenomenon under investigation-newspapers dropping their print edition and going online-only-was too uncommon to support a wider comparative study. The case study approach offered a means to describe, in some detail, this novel case, and to analyse its implications for the future of news in print.…”
mentioning
confidence: 99%